2019
DOI: 10.5604/01.3001.0012.8312
|View full text |Cite
|
Sign up to set email alerts
|

Special Ceramics in Multilayer Ballistic Protection Systems

Abstract: The paper presents some questions of designing and testing for modern ballistic protecting screens and applied materials especially such as ceramics. Continuous development of present ballistic composite materials enforces the optimisation of existing solutions for ballistic protections in respect to the mass, thickness and costs of material. In times of technological arm race a reduction of armour weight by 5% is a success. It may be achieved by development of new solutions of armour systems applying the newe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The mechanisms of the projectile’s impact on ceramic ballistic inserts described in the literature indicated that the basic role of ceramics is to blunt the tip of the projectile, break it into fragments, and absorb some of its energy through brittle fracture of the ceramic elements of the ballistic composite. It was also determined that the role of a composite made of compressed polyethylene or para-aramid layers, to which a ceramic layer is attached, is to retain the projectile core fragments through elastic deformation and absorption of kinetic energy [ 35 ]. Energy absorption occurs through a combination of deformation, fiber pull-out, and delamination of the composite [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of the projectile’s impact on ceramic ballistic inserts described in the literature indicated that the basic role of ceramics is to blunt the tip of the projectile, break it into fragments, and absorb some of its energy through brittle fracture of the ceramic elements of the ballistic composite. It was also determined that the role of a composite made of compressed polyethylene or para-aramid layers, to which a ceramic layer is attached, is to retain the projectile core fragments through elastic deformation and absorption of kinetic energy [ 35 ]. Energy absorption occurs through a combination of deformation, fiber pull-out, and delamination of the composite [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The destruction mechanism of ceramic elements was also the subject of research by Fejdys et al [ 5 ], Cegla [ 35 ], Hogan et al [ 37 ], Magier [ 38 ], and Reddy et al [ 39 ]. Based on the situation observed in Figure 4 c,d, it can be determined that the ceramic layer of the hard ballistic insert (composite system 2) played an analogous role, as indicated in the above literature data.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of rupture of ceramic elements and their influence on ballistic resistance was analyzed in previous studies. Cegła et al [60] pointed out that the role of ceramics is to blunt the bullet's blade, break it into smaller fragments, and absorb some of its energy through fracture. He also stated that the role of a composite made of fibrous material such as UHMWPE or para-aramid pre-impregnate, to which a ceramic layer is attached, is to stop fragments of the bullet core by elastic deformation and absorption of kinetic energy.…”
Section: Fragmentation Resistance Test Resultsmentioning
confidence: 99%
“…Therefore, it is important that the front layer of ceramics is as hard as possible [61,62]. Moreover, in the construction of the layered armor, a very important role is played by the adhesive layer between the ceramics and the fibrous substrate, which must be strong enough to ensure that after a hit, the undamaged areas of the ceramics layer and the substrate remain bound together [60].…”
Section: Fragmentation Resistance Test Resultsmentioning
confidence: 99%